ANALISIS PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM PEMBELAJARAN MATEMATIKA SDN SAWAH BESAR 01 SEMARANG - Rizky M. Anas; Joko Sulianto; Kartinah; Theresia Sawitri (STKIP Subang, 2023)
The purpose of this study is to identify the implementation of the Problem Based Learning model used by teachers in teaching Integrated mathematic in the fourth grade of SDN Sawahbesar 01 Semarang. This research uses a descriptive qualitative method. Data is collected through observation and documentation. All fourth-grade students, consisting of 14 male students and 14 female students, are involved as research participants. Based on the research findings, it is found that the Problem Based Learning model used in mathematic teaching at SDN Sawahbesar 01 Semarang has been implemented well and has followed the 5 phases in the PBL cycle. Positive feedback from students towards problem-based learning indicates that students are able to learn using this PBL model. Based on the assessment of the implementation of learning steps and student involvement in problem-solving, the implementation of the problem-based learning model in SDN Sawahbesar Semarang for fourth-grade students is considered successful.